ONYCHOMYCOSIS FINGER AND TOE NAIL BY CRYPTOCOCCUS LAURENTII.T VERRUCOSSUM AND CANDIDA SP - Widasmara, Dhelya; Sari, Diane Tantia (Institute of Topical Disease Universitas Airlangga, 2018)
Onychomycosis is the most common nail disease and contributes to 50% of all cause of onychodystropy. Onychomycosis cases due to Cryptoccus laurentii and Trychophyton spp. are quite rare. The most common cause of onychomycosis reported in Indonesia is Candida sp. Risk factors for onychomycosis include moisture, occlusion, nail trauma, decreased immunity, slow nail growth, wide nail surface, and genetic factors. Old age, cancer, psoriasis, dermatophyte infection at other sites is also a risk factor. A 54 year-old woman, with brittle nails and cracked palms since 6 months before came to outpatient clinic. She is a farmer and work in the rice fields without gloves daily; she also rarely wash her hands after work. Dermatologic examination of all right and left finger nail is revealed yellow, white, and some blackish discoloration, subungual hyperkeratotic, onycholysis, and onychodystrophy. In the right and left palm, revealed multiple erythematous and yellow-white hyperkeratotic plaques, with fissures and rough scales. From nail clippings, a 20% KOH examination revealed long branching hyphae, periodic Acid-Schiff (PAS) staining revealed spores, and fungal culture revealed growth of Criptococcus laurentii and Trichophyton spp. colonies. We gave itraconazole pulse dose: 2 x 200 mg tablet orally per day for a week every month. Other treatment was using 20% urea cream. Follow up at 8 weeks after therapy is showed clinical and mycologic improvement. The incidence of onychomycosis due to Cryptoccus laurentii and Trychophyton spp. is still rare. Thepredisposing factor of infection in these case is suspected due to old age and her habitual contact with the paddy fields without gloves and rarely wash her hand after work.